Wounds and Words: Trauma, Identity, and the Writer’s Weapon in Salman Rushdie’s Knife: Meditations After an Attempted Murder (Shaheed Smriti Journal, 2025)
Salman Rushdie’s Knife: Meditations After an Attempted Murder (2024) offers a profound exploration of survival, identity, and literary defiance in the wake of a near-fatal attack. This memoir recounts the 2022 stabbing of Rushdie on stage in New York, an event that reignited decades-long threats stemming from the 1989 fatwa following the publication of The Satanic Verses. Far from presenting a simple narrative of victimhood, Knife transforms trauma into a reflective, multidimensional literary work that interrogates the ethical, political, and existential dimensions of storytelling. Through fragmented memory, metafictional reflection, and philosophical musings,Rushdie illustrates how narrative functions simultaneously as a shield and a weapon—protecting the wounded self while resisting ideological extremism and cultural censorship.This article examines Knife using the frameworks of trauma theory, postcolonial critique, and autobiography. Drawing on Cathy Caruth’s theories of trauma as belated and recursive experience, the paper explores how Rushdie’s non-linear, episodic narrative mirrors the psychological disruptions caused by violence while facilitating the reclamation of narrative authority. Through Homi Bhabha’s concept of the “third space,” the study situates Rushdie’s identity as hybrid and liminal, navigating between cultures, ideologies, and diasporic experience. The memoir also engages with the ethical responsibilities of writers, emphasizing the burdens and stakes of defending freedom of expression in a world marked by ideological polarization, religiousextremism, and political censorship.Furthermore, the study highlights the role of intimate relationships, particularly with Rushdie’s wife, Rachel Eliza Griffiths, in fostering resilience, creative collaboration, and human connection amid trauma. By integrating personal vulnerability with broader philosophical, cultural, and political reflection, Knife emerges as both a postcolonial and universal meditation on survival, artistic creation, and the transformative power of storytelling. Ultimately, the memoir demonstrates that writing is not merely a literary exercise but a necessary act of resistance, healing, and identity Shaheed Smriti Journal-202557 reclamation, affirming the enduring importance of words as tools for resilience, empowerment, and ethical engagement in the contemporary world.